A proposed an interactive reliable aggregated photovoltaic cell for a longer time solar energy extraction - El Sayed Soliman; Hamdy Abd El-Halim; Amr Refky (Institute of Advanced Engineering and Science, 2022)
The higher solar energy urges to maximize the solar energy extraction and utilization. This paper aim is to propose a new technique for extending the daily extraction time via a proposed aggregated PV cell. This system idea is using group of the photovoltaic (PV) cells to behave as an interactive regulated cell according to the series or parallel connections, it can call it an aggregated cell. This can be realized by interactive switching system according to the single cell output voltage. Six 6V PV cells are used for configuring the proposed single aggregated 6V PV cell. The technique depends on both single-cell number and their interconnections pattern. Switching the panel connection between the fully series cells to full parallel ones according to either sunlight states or the single-cell output is automatically achieved using an interactive control system. This system includes a voltage sensor that implements the suitable switching pattern for the aggregated cell. The ripple voltages during both morning and afternoon low sun times, as well as due to any other reason such as the lower clouds are efficiently eliminated. The simulated and the experimental results show in a satisfactory agreement the proposed aggregated PV cell validation.